Effect of acidic solutions on the microhardness of dentin and set OrthoMTA and their cytotoxicity on murine macrophage - Soram Oh; Hiran Perinpanayagam; Yoon Lee; Jae-Won Kum; Yeon-Jee Yoo; Sang-Min Lim; Seok Woo Chang; Won-Jun Shon; Woocheol Lee; Seung-Ho Baek; Kee-Yeon Kum (Korean Academy of Conservative Dentistry, 2016)
Objectives To evaluate the effects of three acids on the microhardness of set mineral trioxide aggregate (MTA) and root dentin, and cytotoxicity on murine macrophage. Materials and Methods OrthoMTA (BioMTA) was mixed and packed into the human root dentin blocks of 1.5 mm diameter and 5 mm height. Four groups, each of ten roots, were exposed to 10% citric acid (CA), 5% glycolic acid (GA), 17% ethylenediaminetetraacetic acid (EDTA), and saline for five minutes after setting of the OrthoMTA. Vickers surface microhardness of set MTA and dentin was measured before and after exposure to solutions, and compared between groups using one-way ANOVA with Tukey test. The microhardness value of each group was analyzed using student t test. Acid-treated OrthoMTA and dentin was examined by scanning electron microscope (SEM). Cell viability of tested solutions was assessed using WST-8 assay and murine macrophage. Results Three test solutions reduced microhardness of dentin. 17% EDTA demonstrated severe dentinal erosion, significantly reduced the dentinal microhardness compared to 10% CA (p = 0.034) or 5% GA (p = 0.006). 10% CA or 5% GA significantly reduced the surface microhardness of set MTA compared to 17% EDTA and saline (p < 0.001). Acid-treated OrthoMTA demonstrated microporous structure with destruction of globular crystal. EDTA exhibited significantly more cellular toxicity than the other acidic solutions at diluted concentrations (0.2, 0.5, 1.0%). Conclusions Tested acidic solutions reduced microhardness of root dentin. Five minute's application of 10% CA and 5% GA significantly reduced the microhardness of set OrthoMTA with lower cellular cytotoxicity compared to 17% EDTA.